Medicine dispenser with alarm and alert message using GSM - Md Ropizan, Mohd Ikram Hanafi; Rahmat Talib, (Evolution in Electrical and Electronic Engineering, 2023)
This report presents a project that was undertaken against the background of elderly people frequently forgetting to take their medicines as directed and aiming to create a medication dispenser and reminder system to address this issue. The study aims to increase medication adherence and reduce potential health risks. The medication dispenser was created with therequirements of elderly people in mind, particularly those who have visual and auditory problems. The project makes use of Arduino MEGA for software programming and integrates a number of hardware elements, including acrylic sheets, plastic containers, an LCD display, LED indicators, a servo motor, and an IR sensor. The result of the medicine dispenser project is afunctional prototype that effectively addresses the problem of medication adherence among elderly individuals. It successfully reminds older people to take their medications at the designated time and in the correct dosage, ultimately improving their overall well-being.